Clinical and Pathological Findings of Suspected Cases of Peritoneal Endometriotic Lesions - Aneela Siddiqui, Hamda Shah, Sumera Brohi, Urwa Sarwar, Arjumand, Imran Mehboob Baig (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the clinical and pathological findings of suspected cases of peritoneal endometriotic lesions. Study Design: Cross-sectional/Observational study Place and Duration: Shaikhzaid women hospital larkana, From: Jan, 2021 to June, 2021 Methods: There were 88 females were presented in this study. Females were aged between 18-55 years. Informed permission was obtained before obtaining demographic information such as age, BMI, and symptoms. Included patients had confirmed peritoneal endometriotic lesions. All the suspected cases of peritoneal endometriotic lesion were underwent for biopsies. Numerous endometriotic biopsies were analyzed using mixed effects logistic regression in order to account for various patients and multiple endometriotic gland patterns. Pathological and clinical outcomes among cases were measured. We used SPSS 21.0 to analyze complete data. Results: Among 88 cases, 30 (34.1%) were aged between 18-28 years, 37(42.05%) were aged between 29-38 years and the rest were 21 (23.9%) were aged > 38 years. Mean BMI of the females was 23.2±14.25 kg/m2. Dysmenorrhea was the most common symptoms found in 32 (36.4%) cases, followed by deep dyspareunia in 26 (29.5%) cases, chronic pelvic pain in 18 (20.5%) cases and painful defecation in 12 (13.6%) cases. Frequency of endometriosis was 40 (45.5%) by pathological findings. Majority was undiagnostic biopsies among 58 (65.9%) cases and diagnostic biopsies were among 30 (34.1%) cases. Among undiagnostic biopsies, chronic inflammation found in 18 (31.03%), dystrophic calcifications in 15 (25.9%) cases, hemosiderin-laden macrophages (HLM) in 13 (22.4%) cases, vascular proliferation 10 (17.2%) and adhesions were 10 (17.2%). HLM (P=0.002) and pseudodecidualization (P=0.03) were more often seen in diagnostic biopsies (P=0.05) as were blue/black clinical appearances (P=0.03). Conclusion: We found that individuals with a strong clinical suspicion of endometriosis show a variety of histologic abnormalities, with fewer than half satisfying current histopathologic criteria. Given the diverse histopathologic appearance, more study may be necessary, especially for lesions with primarily vascular characteristics.